Peran KPU dalam Meningkatkan Partisipasi Penyandang Disabilitas pada Pilkada 2024 di Kota Bitung - Susi Susanti Hulu; Maria Heny Pratiknjo; Mahyudin Damis (Universitas Lambung Mangkurat, 2025)
This study aims to critically analyze the role of the General Elections Commission (KPU) of Bitung City in enhancing the political participation of persons with disabilities during the 2024 regional elections (Pilkada). Within the framework of political anthropology, KPU is not merely seen as an electoral institution but as a social actor shaping participatory space for marginalized groups. Using a descriptive qualitative approach, the research was conducted in Bitung City through participatory observation, in-depth interviews, and documentation involving KPU members, election supervisors, and individuals with physical and sensory disabilities. Data were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, display, and conclusion drawing. The findings reveal that while the KPU has made inclusive efforts such as voter registration, accessible education materials, and partial involvement of disabled individuals in the electoral processsignificant structural and cultural barriers remain. These include limited accessibility at polling stations, inadequate inclusive communication strategies, and persistent social stigma. The study concludes that inclusive democracy requires not only institutional reform but also cultural transformation, positioning persons with disabilities not as passive beneficiaries but as active and dignified political subjects